Predictions of cancer incidence in Wielkopolska in 2018 - Godlewski, Dariusz; Wojtyś, Piotr; Antczak, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study: The cancer incidence in Wielkopolska in 2008 was one of the highest in the country and was higher than in Poland by 21% in men and by 14% in women. We can quantify the future burden of cancer from two different perspectives: the number of new cancer cases due to population change and new cases due to risk change. Making predictions of number of new cancer cases in Wielkopolska in 2018. Material and methods : These projections of number of cancer cases, age specific rates and age-standardized rates for 2018 (all cancers and the most frequent cancers for men and women) has been based on the historical trends of cancer incidence in Wielkopolska in 1999-2008 and demographical prognosis of Central Statistical Office using the method of Hakulinen and Dyba. Results : There will be over 8000 new cancer cases in men in Wielkopolska in 2018 and over 7000 in women. Compare to the period 2004-2008 the number of cancer cases will increase by 45% for men and by nearly 30% for women. About 2/3 of the increase in Wielkopolska is predicted to be connected with demography change, 1/3 with risk change. Conclusions : The predicted increase of number of cancer cases in Wielkopolska in 2018 will be the result of: changes in the population (bigger impact of the older age groups), an influence of the risk factors (mainly smoking) and a participation in the screening programs.